„Mały Luter" ze Wschowy. Valerius Herberger (1562-1627) wzorem kaznodziei - Kalbarczyk, Adam (Poznańskie Studia Teologiczne, 2014)
At the turn of the 17th century in the royal town of Wschowa lived and worked the famous Lutheran pastor Valerius Herberger, called “little Luther” – considering his eager preaching, pastoral activity and outstanding theological works. Deserving particular attention is his preaching, which can be regarded as a model also for contemporary, not only Protestant, preachers. They can imitate him in passion for the Gospel of God; in consistent and committed application of the rule that during sermons one should proclaim nothing else but Jesus Christ – the crucified Savior; in being always – even until death – eager, strenuous, uncompromising, brave, creative and joyful witnesses of the faith; in masterful linking in sermons the theological elements with anthropological ones – the word of God with human everyday puzzles; in pastoral, sometimes heroic, care of all the “plagued” of our times; in using in one’s preaching the simple, colorful, pictorial language of listeners’ experiences; and finally in practicing both from the pulpit and during pastoral work the “theology of the heart” which was so characteristic of his sermons. Keywords